ANALISIS PENGAMBILAN KEPUTUSAN DAN MITIGASI TERHADAP KERENTANAN PANTAI (STUDI KASUS : PANTAI PULAU RANGSANG, KABUPATEN KEPULAUAN MERANTI) - Mufriadi Mufriadi; Ari Sandhyavitri; Ferry Fatnanta (Fakultas Teknik Universitas Pasir Pengaraian, 2019)
Rangsang Island is one of the 4 main islands in the Meranti Islands Regency. The location of this island is very strategic because it is directly adjacent to the Malacca Strait so that the island has very high economic value.Abrasion that occurred on Rangsang Island resulted in a lot of losses suffered by people living on the island'scoast, including eroded coconut plantation land, damaged docks, to people who were forced to move because thelocation of the house was very prone to landslides.This final project identifies beaches that have a high level of vulnerability in Pulau Rangsang. Based on theresults of the analysis, Pantai Tanah Merah is the beach with the highest vulnerability value. Installation ofbreakwater structures is effective in preventing unwanted shoreline changes in Tanah Merah. This is becausematerial accessibility is closer to Tanah Merah Beach, prices are relatively cheaper, maintenance is easier so thatit can improve work efficiency